Tunable "soft and stiff", self-healing, recyclable, thermadapt shape memory biomass polymers based on multiple hydrogen bonds and dynamic imine bonds. Issue 21 (20th May 2019) - Song, Fei; Li, Zhaoshuang; Jia, Puyou; Zhang, Meng; Bo, Caiying; Feng, Guodong; Hu, Lihong; Zhou, Yonghong
Abstract : We synthesized "thermadapt" biomass polymers with shape memory, ultrahigh stretchability or rigidity, remarkable self-healing efficiency, recyclability, and reusable adhesiveness. Abstract : The preparation of multifunctional polymer materials from natural renewable resources via a simple method meets ever-expanding practical applications and matches sustainable development strategies. We synthesized a multifunctional polymer with a dual-dynamic three-dimensional (3D) crosslinked network of hydrogen bonds and dynamic imine bonds from epoxy soybean oil and vanillin via a simple preparation process. The as-prepared polymers have controllable mechanical strength between ultrahigh stretchability (strain at break: over 2800%) and rigidity (bending strength: 25.51 ± 0.27 MPa with a strain at break of approximately 2%) via varying imine bonds to readily tailored. They can be used as reusable adhesive. The highly dynamic nature of the hydrogen and imine bonds allows the damaged polymer to self-heal, and it can be re-recycled multiple times. The healed and recycled polymer regains most of its mechanical strength. The polymer exhibits both permanent and temporary shape memory at the same temperature via solid state plasticity, i.e., topological polymer network rearrangement resulting from dynamic bond exchange. Furthermore, our polymers can be used to prepare conductive adhesives/composites that are self-healing, recyclable, and re-shapable.